2017
DOI: 10.1049/hve.2017.0047
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric characteristic of dichlorodifluoromethane (R12) gas and mixture with N 2 /air as an alternative to SF 6 gas

Abstract: In this study, dichlorodifluoromethane (R12) gas and mixtures with nitrogen (N 2) and air at different pressures and mixing ratios have been investigated and showed good alternative to SF 6 gas in terms of high-voltage application. Mixed gases contain R12 gas, they offer good dielectric properties and possibility to be used in low-temperature environment. Synergistic effects and self-recoverability test have been performed. Dielectric strength under quasi-uniform field showed in the order of SF 6 > R12 > N 2 >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The attachment and detachment of electrons depend on the applied field. Equation 1gives relation among dN, N, α, η and dx [8,10].…”
Section: R410a and Its Mixture With Compressed Airmentioning
confidence: 99%
See 1 more Smart Citation
“…The attachment and detachment of electrons depend on the applied field. Equation 1gives relation among dN, N, α, η and dx [8,10].…”
Section: R410a and Its Mixture With Compressed Airmentioning
confidence: 99%
“…The author in [9] has studied R12 gas and air mixture at a band of pressures for the breakdown voltage but analysis was not in detail. In [10], the author has done experimental analysis of R12 gas and Air/N 2 mixture and suggested as an alternative to SF 6 gas. R12 molecules contain fluorine, carbon, and chlorine, which are highly stable, and contributing in the ozone layer destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur hexafluoride (SF 6 ) is widely used in the electrical industry as insulating and switching medium for medium-voltage (MV) and high-voltage (HV) gas insulated switchgear (GIS) due to its excellent properties of high dielectric strength, nontoxicity, chemical inertness, broad operating temperatures range and exceptional arc quenching properties [1]- [3]. However, SF 6 has the global warming potential (GWP) of 23500 CO 2 equivalents and an atmospheric life span about 3200 years, making it the most potent greenhouse gas (GHG) [4], [5]. It is reported that the current equilibrium warming due to SF 6 is 0.004 • C, with a clear tendency to increase [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is also non-flammable as compared to the insulating mineral oils particularly for the indoor environments. However, possessing the aforesaid features and properties SF 6 has been regrettably found to be a damaging greenhouse gas stated by the Kyoto Protocol that it is 22,800 times more harmful than CO 2 for the same masses of both the gases over a time span of 100 years [2,3]. Therefore, SF 6 is included in the prohibited list for ecological safety.…”
Section: Introductionmentioning
confidence: 99%